Evaluation of the Concordance of Cytological Findings Based on the Milan System with Histopathological Findings in Salivary Gland Tumors - Afsharmoghadam, Noushin; Javadi, Abdolreza; Mehrparvar, Golfam; Firoozi Parizi, Mohsen; Saki, Aida (Journal of Otorhinolaryngology and Facial Plastic Surgery, 2023)
Background: The goal of the Milan System for Reporting Salivary Gland Cytopathology (MSRSGC) is to standardize the reporting of salivary gland cytology and guide treatment decisions. Considering the newness of this system and the need for more studies in this regard, the aim of this study was to evaluate the concordance of cytological findings based on the Milan system with histological findings in salivary gland masses. Aim: evaluating salivary gland tumors’ cytological findings of Milan system with histopathological findings. Methods: This diagnostic study was conducted on 94 patients with salivary gland masses were referred to the pathology department of Imam Hossein hospital in 2022. FNA was performed for all patients and cytological classification was done based on the latest classification of the Milan system. Cytological findings were compared with histological findings. Results: In this study 10.6% were diagnosed as non-neoplastic, 18.1% with AUS, 37.2% benign neoplasm, 20.2% with SUMP, 5.3% suspicious for malignancy, and 8.5% were diagnosed as malignant. In the pathology results, 18.1% of patients were non-neoplastic, 56.4% had benign neoplasm, and 25.5% had malignant mass. The agreement coefficient between the two methods based on the Kappa coefficient was 40%, which indicates a relatively good agreement. The correlation coefficient between the two methods was 0.70. Conclusion: It is concluded that there is a relatively good agreement between the Milan system in the cytology of salivary gland neoplasms with pathology findings.